Assessing master's level social work students' attitudes and knowledge of pychotropic medication and attitudes about people with serious mental illness following a classroom intervention - O'Day, Catherine, author; Morgan, George, advisor; Buchan, Victoria, advisor (Colorado State University. Libraries, 2008)
Attitudes towards people with serious mental illness influence the treatment they receive and decisions of policymakers. Social workers have become the largest group of mental health providers in the United States. Therefore, it is important to assess attitudes of social work students who will likely work with people with serious mental illness during their career. Masters level social work students enrolled in a foundation practice course and a concentration course participated in a classroom intervention that provided exposure to people with serious mental illness, explored the use of psychotropic medication, and provided the opportunity to practice assessments with standardized clients. A control group of students enrolled in alternative sections of the same course participated in order to determine if the intervention affected attitude and knowledge change. Three instruments were used in the pre and posttests. Two instruments were used to measure attitudes. The Attitude to Mental Illness scale (Singh, Baxter, Standen, & Duggan, 1998) measured attitudes to people with mental illness. The Attitudes toward Psychotropic Medication scale (Bentley, Farmer, & Phillips, 1991) measured attitudes toward the use of psychotropic medication. In order to measure knowledge about psychotropic medication, the Knowledge Index on Psychotropic Medication questionnaire (Bentley, Fanner & Phillips, 1991) was used. The results of the study indicated that social work students who participated in the study possessed pre-existing fairly high positive attitudes toward people with serious mental illness and psychotropic medication. Therefore, the interventions had no significant change in the pre to posttest scores for both measures. The control group who reported five months to two years of experience had a significantly higher change in their KIPMSW questionnaire posttest scores than the experimental group. Results indicate that the intervention may have been effective for participants who had some experience with people with serious mental illness. This study has implications for social work educators who are responsible for ensuring that future generation of social workers obtain adequate knowledge and attitudes in order to be effective mental health practitioners. Furthermore, the classroom interventions provide examples for teaching a variety of students about specific populations and fields of practice.
Keywords: attitude; Master of Social Work; mental illness; psychotropic medication; social work; social work students; standardized clients; students; social work; higher education